Experimental research of incremental sheet forming based on fastened pre-tensioning. Issue 1 (January 2016) - Zha, G.; Shi, X.; Zhao, W.; Gao, L.; Wu, M.
Abstract Fastened pre-tensioning is conducted on sheet metal prior to incremental forming, thus causing pre-plastic deformation of the sheet metal. To accomplish this process, a 1060H24 aluminum sheet is selected as material, a prosthesis with typical external features as object, and the NHSK1060 incremental sheet forming machine as experimental equipment. By analyzing the forming parts and comparing with conventional incremental sheet forming techniques, fastened pre-tensioning can efficiently improve the springback of incremental forming. Influenced by frictional stress τr, the strain gradually augments with distance from the center. The strain reaches maximum levels around the annular region, which is the pre-tensioning contact area edge of the sheet metal and the support body. The thickness distribution of sheet metal follows cosine law, with fastened pre-tensioning influencing its thickness.